Exploitation of Culinary Plants by Products at Palestinian Argibusiness Partnership Activity (PAPA)Production Site Extraction Of Essential Oils From Herbal Plants - Rozah, Eman; Abd Al-Hadi, Leena; Ali, Leena; Al-Hawah, Yasmeen (My University, 2013)
Sinokrot farms produce several culinary plants for exportation to European countries. These culinary plants are: basil, chervil, chives, coriander, lemon thyme, mint, oregano, parsley, rucolla, rosemary, sorrel, tarragon, and thyme. 30%-50% of these products only meet the export standards. The residue (the loss) which is in high quality are gathered and used as animals food. This project is designed to reuse the loss of culinary plants by rendering them into economical articles. At the first part of the project drying experiments were carried out to produce spices while at this part of graduation project the work is continued to produce essential oils from aromatic plants. Extraction of essential oils from different aromatic plants such as Rosemary, Thyme, Minta and Orange is a promising business. The extraction method used was Steam Distillation which was applied to isolate an Essential Oil from These plants. The steam distillation was successful and the produced oil quantity and quality are identical to that found in literature. The oil color is transparent faint yellow with refractive index is about 1.422 . A sample of approximately 1000(g) of wet green plant was placed in the distiller. The water content in these fresh herbs were about 85-93% and the extracted oil was ranged between (1_3) ml. In general different samples of dried products are used for preparation of pastes, macaroni and pizza sauces, while the essential oil may be used for hundreds of therapeutically and flavoring formulations. It's important to say that the obtained products are pure organic, free from chemicals, this because pesticides and fertilizers were not used at cultivation process. Finally, exploitation of culinary plants by products at PAPA production site is a promising project for different perspectives and it was found that the salvage value of the project after five years is about 6192100NIS.